Applicability of the long‐term uncertainty in measurement (LTUM) method for analytical performance assessment in clinical cytometry laboratories. Issue 3 (16th December 2021) - Dannus, Louis‐Thomas; Mulliez, Aurélien; Berger, Marc; Bourgne, Céline; Veyrat‐Masson, Richard
Abstract: Background: The estimation of uncertainty in measurement for quantitative analyses is an international obligation of the ISO15189 standard for laboratories. The most widespread method is the Internal Quality Control and External Quality Assessment (IQC + EQA). Methods: We compared two methods to assess uncertainty in measurement for the quantification of the number of CD34+ stem cells and of the different lymphocyte subpopulations in blood samples: the IQC + EQA method and the Long‐Term Uncertainty in Measurement (LTUM) method. Results: We focused on the CD3+/CD4+ T lymphocyte subpopulation for a target value of 350 CD3+/CD4+/μl. The range in terms of uncertainty in the measurement of 350 CD3+/CD4+ cells/μl with the IQC + EQA method was [292.8; 407.2]. With the LTUM method, the uncertainty was 19.1% of the measured value. This represented a range of [283.2; 416.9]. Conclusions: The relative uncertainty calculated with the LTUM method can be adapted to any level of the measured parameter. IQC and EQA calculate the absolute uncertainty and need a clustering of values at different levels. This clustering can lead to some approximations in the uncertainty in measurement determination, particularly around the cut‐off values. Unlike previous reports, uncertainty values were higher when calculated with the LTUM than with the IQC + EQA method. However, LTUM might be more representative of the daily routine practice with patient samples.